2022
DOI: 10.35508/forteks.v2i2.6878
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kebutuhan Air pada Daerah Irigasi Air Sagu di Kabupaten Kupang

Abstract: Kabupaten Kupang merupakan salah satu kabupaten di Provinsi Nusa Tenggara Timur yang tergolong iklim tropis kering. Oleh karena itu, pemerintah pusat melalui BWS NT II membangun beberapa daerah irigasi di Kabupaten Kupang salah satunya adalah Daerah Irigasi Air Sagu dengan luas sebesar 163 Ha sebagai alternatif untuk mengoptimalkan ketersediaan air yang terbatas. Penelitian ini bertujuan untuk mengetahui besar debit andalan dengan Metode F. J. Mock dan mengetahui besar kebutuhan air irigasi pada Daerah Irigasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…Another study evaluating the effectiveness of technologies for artificial recharge and rainwater harvesting in Iran suggested that an artificial groundwater recharge system could inject new groundwater in volumes up to hundreds of thousands of m 3 during the dry season and 4.5 x 106 m 3 during the rainy season [8]. Similar studies have been carried out in Timor, Indonesia suggesting the effectiveness of water harvesting method, also known as embung, for many years [10,[14][15][16].…”
Section: Introductionmentioning
confidence: 88%
“…Another study evaluating the effectiveness of technologies for artificial recharge and rainwater harvesting in Iran suggested that an artificial groundwater recharge system could inject new groundwater in volumes up to hundreds of thousands of m 3 during the dry season and 4.5 x 106 m 3 during the rainy season [8]. Similar studies have been carried out in Timor, Indonesia suggesting the effectiveness of water harvesting method, also known as embung, for many years [10,[14][15][16].…”
Section: Introductionmentioning
confidence: 88%
“…Tingkat kebutuhan air irigasi pada muasim tanam I menggunakan metode KP-01 yaitu sebesar 2,169 l/dt/ha dan pada musim tanam II kebutuhan air irigasi sebesar 4,894 l/dt/ha (Wardani & Kurniati, 2022). Neraca air untuk pola tanam padi-padipalawija aternatif 1-alternatif 4 mengalami surplus air dengan surplus air paling tinggi sebesar 2,40 m3 /detik pada perhitungan secara manual dan 4,55 m3 /detik dengan menggunakan Program Cropwat 8.0 (Bunganaen et al, 2022).…”
Section: Kebutuhan Air Tanaman (Cwr)unclassified
“…The selection of the use of equipment and equipment must be adjusted to the physical condition of the river being measured (Beecher, 1995;Agarwal et al, 2000;Bunganaen et al, 2020).…”
Section: Measurement With Current Metermentioning
confidence: 99%